Jinhua Qinggan granules for non-hospitalized COVID-19 patients: A double-blind, placebo-controlled, and randomized controlled trial - Shah, Muhammad Raza; Fatima, Samreen; Khan, Sehrosh Naz; Ullah, Shafi; Himani, Gulshan; Wan, Kelvin; Lin, Timothy; Lau, Johnson Y. N.; Liu, Qingquan; Lam, Dennis S. C. (Frontiers in Medicine, 2022)
Background Key findings from the World Health Organization Expert Meeting on Evaluation of Traditional Chinese Medicine (TCM) in treating coronavirus disease 2019 (COVID-19) reported that TCMs are beneficial, particularly for mild-to-moderate cases. The efficacy of Jinhua Qinggan granules (JHQG) in COVID-19 patients with mild symptoms has yet to be clearly defined. Methods We conducted a phase 2/3, double-blind, randomized, placebo-controlled trial to evaluate the efficacy and safety of treatment with JHQG in mild, non-hospitalized, laboratory-confirmed COVID-19 patients. Participants were randomly assigned to receive 5 g/sacket of JHQG or placebo granules orally thrice daily for 10 days. The primary outcomes were the improvement in clinical symptoms and a proportion tested negative on viral polymerase chain reaction (PCR) after treatment. Secondary outcomes were the time to recover from clinical symptoms and changes in white blood cells (WBC) and acute phase reactants (C-reactive protein (CRP) and ferritin) on the 10th day after treatment initiation. Results A total of 300 patients were randomly assigned to receive JHQG (150 patients) and placebo (150 patients). Baseline characteristics were similar in the two groups. In the modified intention-to-treat analysis, JHQG showed greater clinical efficacy (82.67%) on the 10th day of the trial compared with the placebo group (10.74%; rate difference: 71.93%; 95% CI 64.09–79.76). The proportion of patients with a negative PCR after treatment was comparable (rate difference: −4.67%; 95% CI −15.76 to 6.42). In contrast, all changes in WBC, ferritin, and CRP levels showed a statistically significant decline in JHQG (P ≤ 0.044) after treatment, but not the latter in placebo (P = 0.077). The median time to recovery of COVID-19-related symptoms including cough, sputum, sore throat, dyspnea, headache, nasal obstruction, fatigue, and myalgia was shorter in the JHQG group compared to the placebo group (P < 0.001 for all). Three patients experienced mild-to-moderate adverse events (AEs) duringthe treatment period in the JHQG group. Findings were similar between the modified intention-to-treat and the per-protocol analysis that included only patients who reported 100% adherence to the assigned regimen. Conclusion Based on the time to recover from the COVID-19-related symptoms and AEs, it is concluded that JHQG is a safe and effective TCM for symptomatic relief of patients with mild COVID-19. A symptomatic improvement in the JHQG group patients was observed and JHQG use would have important public health implications in such patients. Clinical Trial Registration The Trial was prospectively registered on www.clinicaltrials.gov with registration number: NCT04723524.